Rheological characteristics of water solutions of guar gum - Bakhmach, Volodymyr; Vovkodav, O.; Vovkodav (Obizyuk), Natalia (My University, 2020)
Rheological characteristics of water solutions of guar gum are studied. Mayonnaise is an oil-in-water type emulsion consisting of vegetable oil (50-85%), egg yolk (5-10%), vinegar, salt and seasonings. The emulsion is stabilized by egg yolk phospholipids. Products with a lower content of oil (<50%) may content thickening agents such as starch, pectin, agar-agar, carboxymethylcellulose, milk proteins. Wide possibilities for using guar gum exist in the mayonnaise technology. Stability at low pH values and low salt content, high viscosity solutions at low shear rate and pseudoplastic characteristics make attractive using systems for stabilization. Because of pseudoplastic characteristics, that are inherent to guar gum, the solutions have fluidity and at the same time stay on salads. Low concentrations of guar gum provide high viscosity of sauces at acidic and neutral pH values. Viscosity of solutions is also stable to temperature changes and withstands different long-term storage conditions. Guar gum may be used for partial replacement of starch, stability improvement and adding a feeling of fullness in the mouth. It is established that growth of concentration of guar gum in an aqueous solution causes gradual increase of the flow index. It should also be mentioned thatflow index values are lower than one for all the concentrations, it is typical for pseudoplastic solutions.
Keywords: stabilization; стабілізація; guar gum; гуарова гумка; galactomannan; галактоманнан; rheological properties; реологічні властивості; viscosity; structure; в'язкість; структура; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів